KEPEMIMPINAN AMBIDEXTROUS DI ORGANISASI GEREJA: INTEGRASI EKSPLORASI DAN EKSPLOITASI UNTUK PERTUMBUHAN YANG BERKELANJUTAN - setiabudi, Hengki irawan (Sekolah Tinggi Teologi Pelita Hati, 2025)
Ambidextrous leadership in the context of the church presents a new paradigm that requires leaders to balance innovation exploration with resource exploitation for sustainable organizational growth. This article aims to analyze the role of ambidextrous leadership in church organizations by examining the dynamics between developing new ministries and preserving core church values. Through literature review and case studies of several churches, it was found that leaders who can integrate exploration and exploitation will be able to increase congregational participation, expand the scope of ministry, and strengthen the church's competitiveness amid social and technological changes. The research findings emphasize the importance of adaptive capacity to change, innovation, and resource support in achieving effective ambidextrous leadership. The practical implications of this research provide strategic recommendations for church leaders to integrate innovation and tradition, ensuring relevant and sustainable church growth in the contemporary era.